Digital Ilearning Chain Scheme in Education Blockchain Based - Rii, Kim Beom (Aptisi Transactions On Technopreneurship (ATT), 2022)
In the era of the digital revolution, the use of technology has made technology a major demand, coupled with the development of insight and techniques, technology in this era has been widely used in all scientific fields. In the field of monetary economics, there are payment instruments that can be used to transact both in the form of goods and services. However, nowadays it is difficult to obtain information as technology develops, the term digital transaction appears. Because many activities are carried out manually, such as searching for customer information, entering inventory items, and payment transactions, the required data display time becomes very long for users and in the process of recording reports including paper, notes, receipts, pens, filing cabinets, etc. . equipment when an error occurs during the input process, generally used simultaneously. Therefore, in this paper, the aim of this DLCS (Digital iLearning Chain Scheme) researcher to utilize Bitcoin technology can help overcome the current problem of how to use Bitcoin cryptocurrency technology in the education payment system in Indonesia. This can give birth to a Bitcoin-based scholarship system. This study uses the Blockchain method to build the system, and uses Google Forms to collect information through digital observations and questionnaires. Based on the characteristics of the system, the Slovin formula is used to analyze various aspects of system satisfaction, and the results of 0.840>0.6 are used for processing, which means if alpha>0.6 then the system can be classified as "reliable". The reliability test proved that the evaluation was based on the provided questionnaire.